Econometric Analysis of the Efficiency of Production of Horticultural Products (Eurasian Journal of Humanities and Social Sciences, 2022)
The article reveals the main production factors that affect the increase in the production of horticultural products. In the dissertation work, using a logarithmic-linear model based on the Cobb-Douglas production function, within the framework of the goals and objectives set for the study, as well as their scientific and methodological solutions are substantiated. A forecast was developed for the gross agricultural product of the Tashkent region and innovations introduced into agriculture for 2022-2027.